Towards effective management of an overabundant native bird: The noisy miner - Ross Crates; Paul G. McDonald; Courtney B. Melton; Martine Maron; Dean Ingwersen; Emily Mowat; Max Breckenridge; Liam Murphy; Robert Heinsohn (Conservation Science and Practice, 2023)
Abstract Addressing threats to biodiversity from pest species is a global challenge. One such challenge is to mitigate the impact of an overabundant Australian songbird, the noisy miner Manorina melanocephala, on woodland birds. The overabundance of noisy miners is listed as a key threatening process under federal biodiversity legislation, but current understanding of where and how noisy miner populations can be managed to yield conservation benefits is unclear. We evaluated the effectiveness of noisy miner removal across 12 treatment areas totaling 3913 ha and nine control areas totaling 1487 ha important for the critically endangered regent honeyeater Anthochaera phrygia. Removal of noisy miners significantly reduced their densities in all but one of the treatment areas. In 10 of the 12 treatment areas, noisy miner densities remained below an impact threshold of 0.65–0.83 birds ha−1 for at least 3 to more than 12 months. The percentage of suitable noisy miner habitat in the surrounding landscape was not a strong predictor of noisy miner management success. Regent honeyeaters occupied six treatment areas, nesting successfully in four. The abundance of other songbirds increased post‐miner removal in seven areas, decreased in three, and was mixed in two. Data from the control areas showed some variation in songbird numbers was independent of noisy miner management. We conclude that noisy miners can be managed in areas of high conservation value for a minimum cost of AUD $10 ha−1. Larger treatment areas may be more important than the broader landscape context in maintaining long‐term noisy miner suppression. Standardized, long‐term monitoring is crucial to identify not only the drivers of pest species recolonization but also locations where threats from pests on endangered species can be addressed effectively while minimizing animal welfare and financial costs.